ATTENDIFY : QR based Attendance Management System - Pande, Manthan; Jangra, Harshit; Bhujade, Bhupendra; Nile, Chaitanya; Kadwane, Dr. Ruchi (Journal of Advanced Research in Information Technology, Systems and Management; Vol 9 No 1 (2025): Journal of Advanced Research in Information Technology, Systems and Management, 2025)
Attendify is an advanced, QR-based attendance management system designed to streamline and secure attendance tracking for educational institutions developed with HTML, CSS, Python and local area networking (LAN) technologies, Attendify provides an efficient, modernized approach for tracking student’s presence, minimizing manual errors and preventing instances of proxy attendance. With automated, real-time record-keeping system, Attendify transforms the traditional attendance process into a seamless and reliable experience for both students and educators, ultimately enhancing institutional efficiency and record accuracy.